2014
DOI: 10.1080/01919512.2014.955909
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Factors on High Concentration of Ozone Production with Dielectric Barrier Discharge

Abstract: The gap distance, electrode material, voltage and gas flow velocity were optimized with gas pressure variation of dielectric barrier discharge (DBD) for producing high concentration of ozone. There exists an optimum gas pressure at which the highest ozone concentration is produced with other parameters being fixed. This optimum gas pressure value changes accordingly as the other parameters changed. As the discharge continues at the optimum pressure, the ozone concentration could increase or decrease slowly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The oxidation of the metal electrode in oxygen containing DBDs was already reported elsewhere . Our initial observation regarding the nanoparticle production in O 2 and CO 2 DBD systems was that deposition rates increase at higher flow rates and in higher power regimes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The oxidation of the metal electrode in oxygen containing DBDs was already reported elsewhere . Our initial observation regarding the nanoparticle production in O 2 and CO 2 DBD systems was that deposition rates increase at higher flow rates and in higher power regimes.…”
Section: Discussionsupporting
confidence: 55%
“…The effect of pressure variations between 1 and 3 bar on process efficiency was mainly studied for the production of ozone – the most industrialized application of DBD reactors . In recent works, Yuan et al and Seok et al demonstrated the existence of an optimal pressure for the ozone synthesis at 1.4 bar for air‐fed and 1.5–2 bar for oxygen‐fed systems. Furthermore, studies on nanosecond pulsed Surface Dielectric Barrier Discharge (SDBD) development at pressures between 1 and 6 bar in air give evidence for changing discharge dynamics with increasing pressure .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increasing the gas pressure makes the gas mass flow rate increase indirectly [21]. The decrease in ozone concentration and ozone yield with gas pressure was experimentally confirmed by Boonduang et al [22] and Seok et al [23].…”
Section: Effect Of Gas Pressurementioning
confidence: 82%
“…The position of the OES, having a fixed 10 mm diameter lens (QEPro, Ocean optics inc., Orlando, FL, USA), was 40 mm away from the electrodes. The DBD device that produced high concentrations of active gas was employed for CO 2 plasma-activated gas (PAG) generation, where the operating conditions were optimized with an output power of 800 W at an AC frequency of 30 kHz [20]. To increase the contact area of the powder, a vortex mixer (VM-96A, Lab Companion, Billerica, MA, USA) installed at the bottom was used to stir the power.…”
Section: Methodsmentioning
confidence: 99%